National Educational Standards and the Integration of School Management in accordance with International - Phumphongkhochasorn, Phumphakhawat; Somruay Pindon, Phrapanyarattanakorn; Srichan, Phramaha Wijit; Soremkaew, Sungwan (Asia Pacific Journal of Religions and Cultures, 2021)
Students’ educational quality is the indicator International educational standards are determined to form the educational standards for all Thai educational degrees. It is used as the provisions of school administration where it should be in any points to be school administration which is in line with national standards and markers. The school administration makes the national education results more grow and succeed in all fields. Also, it impels standards of many institutions is in order to make high-quality learners, Internal school administration is of high-quality including knowledge, ability, potential cosmopolitan and comparable features global. All of that is in keeping with the basic education core curriculum in A.D. 2008 objectives which aim at quality learners to be ready for 21st century learners to prepare cope changes in various fields in the future. There is knowledge and ability, which can correlate with a national degree and free education to be the national education. That the national standard and the school administration are coherent and same directions can help our nation to exist on the international stage inclusive educational field and other fields that associate together. All of these render our nation to know the trick, deserve our dignity, side by side, no being exploit, get benefits what should be get and being a good quality of life.